Optimization of fractional freezing process for bioethanol purification - Amran, N.A. (Institute of Physics Publishing, 2020)
A new bioethanol purification method namely fractional freezing (FF) has been introduced to replace the conventional distillation and adsorption methods which require a higher energy and cost demand. The FF process was conducted in a cylindrical crystallizer equipped with a digital stirrer. Response surface methodology (RSM) was applied to optimize the process, and to investigate the effect of coolant temperature and freezing time towards the efficiency of the process which is represented by effective partition constant (K) and purification efficiency (Peff). Subsequently, a validation experiment was conducted to validate the predicted optimum conditions given by RSM. From the result, the optimum and comparative value of K (0.28) and Peff (31.74) were found at coolant temperature of -17Â°C and 65 min freezing time, with error for both responses less than 10 from prediction. Â© Published under licence by IOP Publishing Ltd.